The old rules of marketing are dead 6 new rules to reinvent your brand & reignite your business - Pearson, Timothy R. (New York McGraw-Hill, 2011)
Argues that the new methods of human communication require a new perspective on marketing, outlining a plan to reinvent the marketing industry by applying quantitative data and providing leadership in a new business landscape.
What Memo Did Marketers Miss? -- I. The Core is Everything -- II. You Have Nothing Without the Foundation -- III. There are Many Choices but Only One Customer -- IV. Do the Right Things for the Right Reasons -- V. Infrastructure is More than Just Pipes -- VI. Lead and Others Will Follow -- VII. The Essence of Marketing Today -- Conclusion: the essence of marketing today.
Includes bibliographical references (pages 219-232) and index.
Keywords: Branding (Marketing); Marketing; Customer relations